KARUDIN TARMIZI : TOKOH MASA PRRI 1958 - 1961 DI KABUPATEN PADANG PARIAMAN - Suhari, Febi Rahmanita (RC-INSTITUT, 2019)
Karudin Tarmizi is a figure who has fought in the PRRI era. He is a PRRI figure in Padang Pariaman District. The PRRI lasted from 1958 to 1961. He began the PRRI struggle at the age of 31 years. The guerrilla struggle made him far from the family he loved. This Padang Pariaman Regency, especially in the Sicincin area, is a base for the defense of the central army and also the PKI. The PRRI upheavel in Padanng Pariaman District occurred in this Sicincin area. Karudin Tarmizi and his other colleagues began their struggle from the Kudu area because this area was a very safe area at that time. And the struggle ended in the Sikabu area. This study uses a historical method consisting of four stages namely; First, heuristics which means finding or gathering sources. Second, criticizing sources, namely the sources that have been collected both in the form of objects, written sources and oral sources are then verified or tested through a series of criticism, both internal and external. Third, interpretation namely the historical facts that have been collected have not told much. These facts must be compiled and combined with each other so as to form the story of historical events. Fourth, historiography is the final stage of historical research. The writing of this biography is expected to add to the literacy and knowladge of the community about PRRI figures, especially in Padang Pariaman District.